Modified Green–Lindsay thermoelasticity wave propagation in elastic materials under thermal shocks. Issue 1 (21st August 2020) - Shakeriaski, Farshad; Ghodrat, Maryam; Escobedo-Diaz, Juan; Behnia, Masud
Abstract: In this study, a nonlinear numerical method is presented to solve the governing equations of generalized thermoelasticity in a large deformation domain of an elastic medium subjected to thermal shock. The main focus of the study is on the modified Green–Lindsay thermoelasticity theory, solving strain and temperature rate-dependent model using finite strain theory. To warrant the continuity of the finding responses at the boundary after the applied shock, higher order elements are adopted. An analytical solution is provided to validate the numerical findings and an acceptable agreement between the two presented solutions is obtained. The findings revealed that stress and thermal waves have distinct interactions and a harmonic temperature variation may lead to a systematic uniform stress distribution. Besides, a notable difference in the results predicted by the modified Green–Lindsay model and classic theory is observed. It is also found that the modified Green–Lindsay theory is more efficient in determining the wave propagation phenomenon. Furthermore, the findings established that thermal shock induces tensile stresses in the structure immediately after the shock, and the perceived phenomenon mainly depends on the defined boundary conditions. The results show that the strain rate can have a significant influence on the displacement and stress wave propagation in a structure subjected to thermal shock and these impacts may be more considerable with mechanical loading. Graphical Abstract: